Introducing the Berggruen Governance Index II: Initial results, 2000–2019 - Helmut K. Anheier; Markus Lang; Edward L. Knudsen (Global Policy, 2023)
This article presents an overview of some of the main findings from our analysis of the Berggruen Governance Index for the 2000–2019 period. It first examines overall governance performance across world regions, singles out general trends and identifies top and bottom performers. It then briefly reviews the comparative governance performance of world powers like the United States, Brazil, China, major European countries, India and Russia as well as other selected countries in the post-Soviet space. Finally, we address more analytic questions to show the versatility of the index for hypothesis testing and theoretical purposes.
Keywords: 320